iSALTY as a Framework for Combining Three English Language Learning Methods: State-of-the-Art Research - Kurniawan, Mozes; Wijayaningsih, Lanny; Listyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Early childhood language development is critical, forming the basis for cognitive, social, and emotional growth. Children's brains are particularly receptive to linguistic input during these formative years, which makes them an optimal period for developing language skills, particularly in English. The trend of integrating English language learning in Early Childhood Education (PAUD) has increased rapidly in Indonesia. The main objective of the iSALTY research is to develop and evaluate an innovative learning framework that harmoniously integrates three English language learning methods to increase the effectiveness of the learning process. Using a literature study approach, this research provides a comprehensive review of existing research to advance knowledge in early childhood English teaching. This research used purposive sampling to select 45 references consisting of 12 titles about Audio Lingual Method (ALM), 16 titles about Total Physical Response (TPR), and 17 titles about Storytelling. A structured six-step procedure was followed to ensure a thorough and systematic literature review. This stae of the arts research reveals that integrating ALM, TPR, and Storytelling has the opportunity to form a dynamic and interesting way of teaching and learning. This holistic approach utilizes repetition, contextualization, and physical reinforcement, which effectively enhances children's linguistic abilities in strengthening English language skills. The implications of iSALTY research have the potential to have a significant impact in the context of English language learning at various levels of education.